Enhancement of bioethanol production by a waste biomass-based adsorbent from enzymatic hydrolysis. (1st April 2021) - Hou, Jinju; Zhang, Xiaotong; Zhang, Shudong; Wang, Kainan; Zhang, Qiuzhuo
Abstract: Alkaline pretreatment is an efficient method to destroy the lignocellulose structure of rice straw for bioethanol production. This process generates various toxic compounds, such as ferulic acid, which could inhibit bioethanol production. In this study, a waste biomass-based adsorbent from the enzymatic hydrolysis of rice straw (AEPA250 ) was used for ferulic acid detoxification in the alkali-pretreated hydrolysate. The AEPA250 detoxification process was first optimized by response surface methodology to increase ferulic acid removal, while reducing glucose loss. This optimization of detoxification resulted in 99.268% ferulic acid removal coupled with 3.028% glucose loss. The fermentation processing parameters and bioethanol production for different fermentation systems were evaluated after adopting the optimal AEPA250 detoxification conditions to select the most suitable optimization method. The result revealed that optimized detoxified fermentation with AEPA250 filtration (ODF) system was more suitable for bioethanol production than optimized detoxified fermentation containing AEPA250 (ODFA) system followed by non-detoxified fermentation (NDF) system. A logistic model was applied to further compare the yeast growth kinetics of the ODF and NDF systems. The ODF system had a maximum specific growth rate (μmax ) of 0.532 h −1, indicating that the ODF system possessed greater bioethanol fermentation potential. Metabonomics and transcriptomics analyses were used to identify differentially expressed metabolites and functional genes that contribute to detoxification by the ODF system. AEPA250 was produced by the enzymatic hydrolysis of biomass waste of rice straw in the bioethanol production process, and a self-sufficient bioethanol production system could be established by in-situ AEPA250 detoxification using the ODF system. These results pave the way for the realization of a cleaner bioethanol production process by reducing environmental waste production, exogenous adsorbent use, and the cost of enzymatic hydrolysis residue treatment. Graphical abstract: Image 1 Highlights: The detoxification of ferulic acid by AEPA250 was optimized using RSM method. The production of bioethanol could increase 38.368% by ODF system at 12 h. The ODF system was more effective than ODFA system followed by NDF system. Omics and yeast growth kinetics study revealed the optimized-detoxified mechanism.